2019
DOI: 10.1111/jpy.12820
|View full text |Cite
|
Sign up to set email alerts
|

Family‐level variation in early life‐cycle traits of kelp

Abstract: Temperate kelp forests (Laminarians) are threatened by temperature stress due to ocean warming and photoinhibition due to increased light associated with canopy loss. However, the potential for evolutionary adaptation in kelp to rapid climate change is not well known. This study examined family‐level variation in physiological and photosynthetic traits in the early life‐cycle stages of the ecologically important Australasian kelp Ecklonia radiata and the response of E. radiata families to different temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 97 publications
(198 reference statements)
1
12
0
Order By: Relevance
“…This indicates variation in genotype responses to the MHW treatment, which coincides with emerging evidence suggesting that variation in stress tolerance among different genotypes can contribute to the magnitude of response to extreme events (Wernberg et al 2018, Coleman & Wernberg 2020, Cole man et al 2020a, Gurgel et al 2020. Previous studies on thermal reaction norms have also shown G×E interactions, indicating variation in temperature tolerance among genotypes (Clark et al 2013, Mabin et al 2019, Liesner et al 2020b. For example, Mabin et al (2019) found significant morphological variation in E. radiata gametophytes from different lineages in response to different temperature and light levels, which they linked to possible maternal and genetic effects.…”
Section: G×e Interactionsmentioning
confidence: 88%
See 1 more Smart Citation
“…This indicates variation in genotype responses to the MHW treatment, which coincides with emerging evidence suggesting that variation in stress tolerance among different genotypes can contribute to the magnitude of response to extreme events (Wernberg et al 2018, Coleman & Wernberg 2020, Cole man et al 2020a, Gurgel et al 2020. Previous studies on thermal reaction norms have also shown G×E interactions, indicating variation in temperature tolerance among genotypes (Clark et al 2013, Mabin et al 2019, Liesner et al 2020b. For example, Mabin et al (2019) found significant morphological variation in E. radiata gametophytes from different lineages in response to different temperature and light levels, which they linked to possible maternal and genetic effects.…”
Section: G×e Interactionsmentioning
confidence: 88%
“…Previous studies have examined the influence of genotypes on fitness to environmental stress in marine organisms (Császár et al 2010, Pease et al 2010, Foo et al 2012, including genetic variation in thermal sensitivity among genotypes in kelp populations (Mabin et al 2019, Liesner et al 2020b). These studies have found heritable within-population variation for traits that influence the persistence of populations experiencing warming, suggesting that genetic variation may affect population resilience to heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…Li and Brawley (2004) demonstrated a positive parental effect of warm receptacle environment on Fucus vesiculosus embryo survival during heat stress. Mabin et al (2019a) demonstrated significant variation in morphology between lineages of Ecklonia radiata gametophytes at different temperatures and irradiances, which they attributed to potential parental and genetic effects. The latter further indicates that individual phenotypic variation may play a substantial role in shaping response variability of kelp populations.…”
Section: Introductionmentioning
confidence: 99%
“…The life cycle of kelps (order Laminariales) consists of two phases, a microscopic haploid gametophyte ( n ), alternating with a macroscopic diploid sporophyte ( 2n ), which respond differently to environmental variables [ 21 ]. Specifically, the spores and gametophytes are more sensitive to chemical pollution exposure than the adult sporophytes [ 17 , 22 ].…”
Section: Introductionmentioning
confidence: 99%